2017
DOI: 10.1186/s12936-017-1994-6
|View full text |Cite
|
Sign up to set email alerts
|

The development of an ivermectin-based attractive toxic sugar bait (ATSB) to target Anopheles arabiensis

Abstract: BackgroundAn increasing number of countries in sub-Saharan Africa are moving towards malaria-elimination, mostly thanks to successful vector control campaigns. However, elimination has proven challenging, resulting in the persistence of malaria transmission. It is now accepted that in order to eliminate malaria, new complementary vector control approaches must be developed. This study describes the development of a sugar-baited resting place containing a toxic dose of ivermectin for the control of Anopheles ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 42 publications
2
51
0
Order By: Relevance
“…gambiae, show are attracted to certain plants (Gouagna et al 2010;Manda et al 2007;Mauer and Rowley 1999;Müller et al 2011). In addition to other plant parts such as flowers and leaves, female mosquitoes showed an obvious attraction to the odors of fruits (Hien et al 2016;Müller et al 2011;Yu et al 2017) and fruit juices (Tenywa et al 2017). This is consistent with our results as An.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…gambiae, show are attracted to certain plants (Gouagna et al 2010;Manda et al 2007;Mauer and Rowley 1999;Müller et al 2011). In addition to other plant parts such as flowers and leaves, female mosquitoes showed an obvious attraction to the odors of fruits (Hien et al 2016;Müller et al 2011;Yu et al 2017) and fruit juices (Tenywa et al 2017). This is consistent with our results as An.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, attractants from fruit juice were used to lure mosquitoes to an insecticide as a development of ATSB (Beier et al 2012). Tenywa et al (2017) reported that Anopheles spp. mosquitoes were attracted to juice from subtropical fruits such as guava, mango and banana.…”
Section: Introductionmentioning
confidence: 99%
“…Current commercial traps are expensive and bulky as they require a CO 2 source and usually contain foul smelling synergists. Alternative traps made from recycled materials [108], such as buckets (for example the Gravid Aedes Trap) [109] and sticky traps, using products available in the home, such as castor oil [110], need further investigation as these can provide a low-cost and practical solution for vector control in developing countries. The focus of most of the research has primarily been on single olfactory compounds or blends containing less than five compounds.…”
Section: Discussionmentioning
confidence: 99%
“…An attractive-toxic sugar bait was developed and tested inside a biodome at the Ifakara Health Institute [ 11 ]. The prototype tested in the semi-field demonstrated an ability to attract at least 50% of the free flying Anopheles arabiensis and that these were most likely to choose to feed on a sugar bait placed outdoors amidst vegetation although it would also feed indoors if humans were protected by a bed net [ 11 ]. The ATSBs that were distributed contained 0.01% ivermectin in 10% sugar solution, and its structure was made using 100% recycled materials readily available in rural Tanzania (Fig.…”
Section: Methodsmentioning
confidence: 99%